2020
DOI: 10.1038/s41467-020-18392-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and mitigation of gene expression burden in mammalian cells

Abstract: Despite recent advances in circuit engineering, the design of genetic networks in mammalian cells is still painstakingly slow and fraught with inexplicable failures. Here, we demonstrate that transiently expressed genes in mammalian cells compete for limited transcriptional and translational resources. This competition results in the coupling of otherwise independent exogenous and endogenous genes, creating a divergence between intended and actual function. Guided by a resource-aware mathematical model, we ide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
172
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(191 citation statements)
references
References 68 publications
0
172
0
Order By: Relevance
“…The general problem of resource competition in genetic circuits has been widely studied in the context of competition for translation resources in bacteria 7,20,21 and for transcription resources in mammalian cells 22,23 . In particular, studies in bacteria have shown that the effects of ribosome competition on the I/O response of a genetic circuit can be very subtle, yet dramatic, as the inner circuit's modules compete with one another for ribosomes 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The general problem of resource competition in genetic circuits has been widely studied in the context of competition for translation resources in bacteria 7,20,21 and for transcription resources in mammalian cells 22,23 . In particular, studies in bacteria have shown that the effects of ribosome competition on the I/O response of a genetic circuit can be very subtle, yet dramatic, as the inner circuit's modules compete with one another for ribosomes 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The response of expressed genes to their extracellular (or intracellular) inputs are often stochastic and thus imprecise across individual cells 75,76 . In addition, the intracellular context affects the level of gene expression induced by signaling 40,41 , due to factors such as off-target interactions among engineered genes 58 or resource competition among genes 73,77,78 . To remedy these issues and enable the construction of genetic devices that enforce precise and robust signaling responses across cells, we developed a phosphorylation-based negative feedback controller of gene expression (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, only the use of the weaker P PGK promoter, but not the stronger P hEF1α promoter, afforded a functional gene switch. We attribute this effect to competition between transgenes for the cellular transcriptional and translational resources (Frei et al, 2020); the stronger P EF1a promoter might sequester resources that would otherwise be available for expression of the reporter gene. Additional expression of the transporter SMIT1 increased the fold switching in CHO‐K1 cells ( p = .0397), in accordance with the anticipated facilitation of l ‐glucose transport across the plasma membrane.…”
Section: Resultsmentioning
confidence: 99%